2015
DOI: 10.18632/oncotarget.5687
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 regulates cancer cell metabolism via scavenging Nrf2 and suppressing MnSOD-driven glycolysis

Abstract: Aerobic glycolysis is an indispensable component of aggressive cancer cell metabolism. It also distinguishes cancer cells from most healthy cell types in the body. Particularly for this reason, targeting the metabolism to improve treatment outcomes has long been perceived as a potentially valuable strategy. In practice, however, our limited knowledge of why and how metabolic reprogramming occurs has prevented progress towards therapeutic interventions that exploit the metabolic peculiarities of tumors. We rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 40 publications
7
41
0
Order By: Relevance
“…This scenario is consistent with recent findings showing that a loss of caveolin-1 expression in breast cancer cells activates nuclear erythroid 2 p45-related factor-2 (Nrf2) and promotes manganese-dependent superoxide dismutase (MnSOD)-induced glycolysis and that reconstitution of caveolin-1 expression in caveolin-1-negative breast cancer cells suppresses Nrf2, reduces MnSOD expression, inhibits glycolysis and enhances mitochondria-dependent ATP production [41]. Interestingly, we have previously demonstrated that caveolin-1 is an endogenous inhibitor of Nrf2 and that Nrf2 is hyperactivated in caveolin-1 null MEFs [28].…”
Section: Discussionsupporting
confidence: 92%
“…This scenario is consistent with recent findings showing that a loss of caveolin-1 expression in breast cancer cells activates nuclear erythroid 2 p45-related factor-2 (Nrf2) and promotes manganese-dependent superoxide dismutase (MnSOD)-induced glycolysis and that reconstitution of caveolin-1 expression in caveolin-1-negative breast cancer cells suppresses Nrf2, reduces MnSOD expression, inhibits glycolysis and enhances mitochondria-dependent ATP production [41]. Interestingly, we have previously demonstrated that caveolin-1 is an endogenous inhibitor of Nrf2 and that Nrf2 is hyperactivated in caveolin-1 null MEFs [28].…”
Section: Discussionsupporting
confidence: 92%
“…The process is regulated by caveolin-1, which binds directly to both NRF2 and KEAP1, and impedes on NRF2 activation and hence on the glycolytic shift. This is apparently one explanation why glycolytic tumors, which are generally more aggressive, have a caveolin-1 low /Mn-superoxide dismutase high phenotype (Hart et al, 2016). NRF2 can also drive glucose and glutamine toward anabolic pathways required for tumor cell proliferation (Mitsuishi et al, 2012).…”
Section: Systems Medicine Approach To Nrf2 In Chronic Diseasesmentioning
confidence: 99%
“…In invasive ductal carcinoma, CAV1 is reduced at the early stage of progression and predicts poor survival outcome. Mechanistically, reduced CAV1 expression enabled the induction of transcription factor NRF2 (NF-E2-related factor 2), which activates anti-oxidant manganese superoxide dismutase (MnSOD) that triggers AMPK-dependent glycolysis [56]. As a proof, ectopic expression of CAV1 in invasive ductal carcinoma cells (MCF7) suppressed NRF2 expression, the induction of MnSOD, and decreased aerobic glycolytic phenotype as measured by extracellular acidification and lactate output [56].…”
Section: Cav1 In Glycolysismentioning
confidence: 99%